Gen Z Impulse Buying behavior : The Moderating Role of UI/UX - Revival Xavier Iskandar; Putu Irma Yunita (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study explores the dynamics of promotion, price, positive emotion, and impulse buying within the environment of TikTok Shop, focusing particularly on how these marketing and psychological factors interact in a social commerce setting. The research also investigates the role of UI/UX as a potential moderating variable in these relationships. Using a quantitative design and analyzed through the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach, the study evaluates both direct and mediated pathways among the constructs. The discussion emphasizes how promotional exposure, pricing perceptions, and emotional responses shape consumer behavior, and how UI/UX is conceptually positioned to influence these effects. Through analytical interpretation, the study highlights the theoretical and practical contributions of examining impulse buying in rapidly growing social commerce platforms, offering a deeper understanding of the mechanisms through which marketing stimuli and user experience may interact